Transformation of an ordinary ring road intersection into a turbo ring intersection: bandwidth comparison - V. I. Rassokha; N. A. Nikitin (Интеллект. Инновации. Инвестиции, 2020)
In large cities, a situation often arises when roundabout intersections of highways no longer cope with the passage of traffic flows. The main reasons for this problem are the inconsistency of the potential traffic capacity of the roundabout with real traffic flows, as well as the lack of knowledge and skills of drivers on the roundabout carriageway. To reduce the influence of the human factor, various solutions are proposed, but, as practice has shown, ducted roundabouts or «turbo rings» are the most effective. A feature of this configuration of the carriageway is the predictability of driver behavior due to the physical separation of lanes for traffic. In a number of countries, turbo ring intersections have already been put into operation, which made it possible to confirm the alleged advantages of this configuration: the absence of changeover maneuvers on the ring carriageway, the need to give way to a maximum of two traffic flows, and a decrease in the average travel speed along the ring intersection. The aim of this study was to compare the performance of the existing threelane intersection, characterized by a predominance of lefthand turn flow during rush hours, and the developed design of the turbo ring interchange. Empirical data on traffic flows and length of queues, as well as a matrix of correspondences, were used to calibrate the computer micromodel. Micromodeling was carried out by means of: specifying the matrix of correspondences, taking into account the distribution of the traffic flow in time; setting the rules of priority, speed of approach to the intersection and speed reduction zones; development of scenarios for the analysis of morning and evening rush hours, fluctuations in traffic flows in time. Performance comparisons were made for the node as a whole, as well as for the selected busiest routes in terms of average and maximum congestion lengths, average latency and downtime. To assess the performance of the intersections, it was proposed to use foreign methods for assessing the capacity based on the mathematical models of Bowie, Hagring and Fortine. It was revealed that the transformation of the existing circular intersection into a turbo ring made it possible not only to increase the throughput of the node, but also to reduce congestion at the entrances and exits, which determines the practical significance of the study. To study the possibility of integrating the methodology for assessing the throughput, considered in the article, into the domestic method for choosing the type of intersections, which is the basis of regulatory and technical documents. The ultimate goal of the study is to create a new methodology for assessing the throughput of circular intersections of various types, including taking into account the peculiarities of the functioning of circular intersections on the territory of the Russian Federation.